2020
DOI: 10.1021/acs.jpclett.0c00034
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Magnetism and Photocurrent in Mn-Doped Organic–Inorganic Perovskites

Abstract: Organic–inorganic perovskites have attracted increasing attention in recent years owing to their excellent optoelectronic properties and photovoltaic performance. In this work, the prototypical hybrid perovskite CH3NH3PbI3 is turned into a ferromagnetic material by doping Mn, which enables simultaneous control of both charge and spin of electrons. The room-temperature ferromagnetism originates from the double exchange interaction between Mn2+–I––Mn3+ ions. Furthermore, it is discovered that the magnetic field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 59 publications
3
47
0
Order By: Relevance
“…Ren et al reported that Mn-doped MAPbI 3 presented the magnetism at room temperature, which originals from the double-exchange mechanism taking place in the Mn 2+ -I-Mn 3+ framework. [82] Moreover, the application of MF can effectively modulate the photovoltaic performance of PSCs owing to the new Mn-endowed magnetic degree of freedom. Dou et al found that the internal magnetic parameter B 0 can be decreased from 401.41 to 180.18 mT with decreasing the MA/FA ratio, indicating that the SOC in PSCs was changed through changing the internal dipole moment.…”
Section: Effect Of Magnetic Field On Photovoltaic Performancementioning
confidence: 99%
“…Ren et al reported that Mn-doped MAPbI 3 presented the magnetism at room temperature, which originals from the double-exchange mechanism taking place in the Mn 2+ -I-Mn 3+ framework. [82] Moreover, the application of MF can effectively modulate the photovoltaic performance of PSCs owing to the new Mn-endowed magnetic degree of freedom. Dou et al found that the internal magnetic parameter B 0 can be decreased from 401.41 to 180.18 mT with decreasing the MA/FA ratio, indicating that the SOC in PSCs was changed through changing the internal dipole moment.…”
Section: Effect Of Magnetic Field On Photovoltaic Performancementioning
confidence: 99%
“… 47 The presence of Mn 3+ in perovskite samples was also invoked to rationalize the ferromagnetic coupling in MAPb 1– x Mn x I 3 , proposed to arise from Mn 2+ –I – –Mn 3+ motifs. 48 Very recently, Babu et al revealed the formation of a transient charge-transfer state in Mn:CsPbBr 3 , suggesting that a spin-allowed charge-transfer process (concurrent to energy transfer) related to Mn 3+ formation is likely to occur. 49 …”
mentioning
confidence: 99%
“…Perovskite magnetic materials have been studied for almost 50 years. These systems offer a degree of chemical flexibility which allows the relation between the oxides structure, and electronic and magnetic properties that can be controlled in various ways, such as: Doping [61][62][63], magnetic field [64][65][66], electric field [67,68], temperature [69][70][71], pressure, and photoexcitation [72][73][74][75]. Research on these compounds has revealed the relevant phe-nomenon of magnetoresistance [76][77][78][79], and has led to the formulation of important physical concepts such as double exchange [1] and the Jahn-Teller polaron [80].…”
Section: Perovskite Compounds: General Concepts and Applicative Indicmentioning
confidence: 99%